A clinicopathologic review and obstetric outcome of uterine smooth muscle tumor of uncertain malignant potential (STUMP) in a single institution. (September 2018) - Ha, Hyeong In; Choi, Min Chul; Heo, Jin Hyung; Kim, Kyoung Ah; Jung, Sang Geun; Park, Hyun; Joo, Won Duk; Song, Seung Hun; Kim, Tae Hoen; Lee, Chan
Abstract: Objectives: The present study aimed to analyze the clinicopathologic features and treatment of uSTUMP in a single institution. In addition, we described the obstetric outcomes after uterine-preserving surgery for uSTUMP. Methods and materials: A retrospective chart review was performed of patients diagnosed with uSTUMP between January 2000 and February 2018 at the Comprehensive Gynecologic Cancer Center, CHA Bundang Medical Center. We obtained data on the patients' demographics, treatment, therapeutic results, time to recurrence, disease-free and overall survival, and subsequent obstetric outcomes. The central pathology reviews were carried out by two pathologists specializing in gynecologic oncology. Result: A total of 19 patients diagnosed with uSTUMP were identified and included in the study. The mean age at diagnosis was 41 years (range 28–49 years). Frozen sections were performed in 11 patients including five patients during surgery. Nine of the 19 patients (47.4%) were treated by hysterectomy and 10 patients were initially treated by myomectomy. The mean follow-up period was 47 months (range 6–209 months). Two patients (10.5%; 2/19) experienced recurrence. Although not defined as recurrence in the present study criteria, one patient had a secondary diagnosis of atypical leiomyoma one year after the initial diagnosis of uSTUMP. Seven patients requested uterine-preserving treatment, five of whom wanted to become pregnant. Three of them (3/5; 60%) successfully delivered live birth to full term by Cesarean section without complications such as abortion, preterm delivery or uterine rupture, and tumor recurrence. Conclusions: The present study describes the clinicopathologic data of uSTUMP patients. Our results suggest a uSTUMP recurrence of 10.5%, comparable to previous reports. Although there is a possibility of malignant recurrence, fertility-preserving management is worth attempting because of relatively low affected age with careful close follow-up.